Morphological aspects of neuromuscular junctions and gene expression of nicotinic acetylcholine receptors (nAChRs) in skeletal muscle of rats with heart failure - Tome de Souza, Paula Aiello [UNESP]; Matheus, Selma Maria Michelin [UNESP]; Castan, Eduardo Paulino [UNESP]; Salome Campos, Dijon Henrique [UNESP]; Cicogna, Antonio Carlos [UNESP]; Carvalho, Robson Francisco [UNESP]; Dal-Pai-Silva, Maeli [UNESP] (Springer, 2011)
HF is syndrome initiated by a reduction in cardiac function and it is characterized by the activation of compensatory mechanisms. Muscular fatigue and dyspnoea are the more common symptoms in HF; these may be due in part to specific skeletal muscle myopathy characterized by reduced oxidative capacity, a shift from slow fatigue resistant type I to fast less fatigue resistant type II fibers and downregulation of myogenic regulatory factors (MRFs) gene expression that can regulate gene expression of nicotinic acetylcholine receptors (nAChRs). In chronic heart failure, skeletal muscle phenotypic changes could influence the maintenance of the neuromuscular junction morphology and nAChRs gene expression during this syndrome. Two groups of rats were studied: control (CT) and Heart Failure (HF), induced by a single intraperitoneal injection of monocrotaline (MCT). At the end of the experiment, HF was evaluated by clinical signs and animals were sacrificed. Soleus (SOL) muscles were removed and processed for morphological, morphometric and molecular NMJ analyses. Our major finding was an up-regulation in the gene expression of the alpha1 and epsilon subunits of nAChR and a spot pattern of nAChR in SOL skeletal muscle in this acute monocrotaline induced HF. Our results suggest a remodeling of nAChR alpha1 and epsilon subunit during heart failure and may provide valuable information for understanding the skeletal muscle myopathy that occurs during this syndrome.
Keywords: Heart failure; Neuromuscular junction; Skeletal muscle; Nicotinic acetylcholine receptors; Gene expression